THE INFLUENCE OF SCHIZOPHRENIA ON DENTAL TREATMENT - Oana Cristina Cretu; Marius Cocu; Elena Rodica Popescu (Romanian Journal of Medical and Dental Education)
This article explores the challenges of providing dental care for patients with schizophrenia, a disorder that can impair communication, reduce cooperation, and lead to poor oral hygiene due to symptoms and medication side effects. Schizophrenia often results in neglected oral health, complicated by factors like dry mouth from antipsychotic medications and irregular dental visits.